Enhancing crop innate immunity: new promising trends - Huang, Pin-Yao; Zimmerli, Laurent (Frontiers in Plant Science, 2014)
Plants are constantly exposed to potentially pathogenic microbes present in their surrounding environment. Due to the activation of the pattern-triggered immunity (PTI) response that largely relies on accurate detection of pathogen- or microbe-associated molecular patterns by pattern-recognition receptors (PRRs), plants are resistant to the majority of potential pathogens. However, adapted pathogens may avoid recognition or repress plant PTI and resulting diseases significantly affect crop yield worldwide. PTI provides protection against a wide range of pathogens. Reinforcement of PTI through genetic engineering may thus generate crops with broad-spectrum field resistance. In this review, new approaches based on fundamental discoveries in PTI to improve crop immunity are discussed. Notably, we highlight recent studies describing the interfamily transfer of PRRs or key regulators of PTI signalling.